Thermal Stability of N,N′-Bis(1-ethylpropyl)perylene-3,4,9,10-tetracarboxdiimide Films on Cu(100) - Moreno López, Juan Carlos (2016)
The thermal stability of N,N′-bis(1-ethylpropyl)-perylene-3,4,9,10-tetracarboxdiimide (EP-PTCDI) thin films deposited on Cu(100) has been characterized by using scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS), and low-energy electron diffraction (LEED). For one monolayer absorption, the molecules arrange with a (34-26) symmetry. After annealing the sample at 500 K, XPS measurements show that the molecules dissociate leaving the PTCDI core of the molecule on the surface. According to that, STM measurements show new images of molecules with the size of the PTCDI core, and without the characteristic ethylpropyl end groups. These remaining molecules cover most of the surface with ordered islands, presenting a different molecular arrangement. With the help of the experimental and simulated LEED patterns, the molecular arrangement can be described by a (-563.53) superstructure and its four rotational equivalents. However, complementary measurements of STM images at different tip-to-sample bias voltages showed variations of the local density of states for molecules absorbed at different absorption sites, reflecting a (-5676) commensurated arrangement.